2013
DOI: 10.4238/2013.august.2.1
|View full text |Cite
|
Sign up to set email alerts
|

GSTM1 and GSTT1 polymorphisms in endometriosis in women from Goiás, Brazil

Abstract: ABSTRACT. Endometriosis is a gynecologic pathology with a high prevalence and unknown etiology. Therefore, an increasing number of studies has been undertaken to search for associations between endometriosis and alterations or polymorphisms in candidate genes, including glutathione S-transferase mu 1 (GSTM1) and glutathione S-transferase theta 1 (GSTT1). We analyzed the frequency of present/absent polymorphisms of GSTM1 and GSTT1 in 50 women diagnosed with endometriosis and in a control group of 46 women witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 15 publications
2
21
0
Order By: Relevance
“…A lower prevalence (27.6%) was reported by Chen et al (1996) in the US. Other researchers detected a GSTM1-null polymorphism prevalence of 74.0% in women (Frare et al, 2013). Similar results showed that the GSTM1-null polymorphism was 73.8% in African-Americans (Weiserbs et al, 2003).…”
Section: Discussionsupporting
confidence: 62%
“…A lower prevalence (27.6%) was reported by Chen et al (1996) in the US. Other researchers detected a GSTM1-null polymorphism prevalence of 74.0% in women (Frare et al, 2013). Similar results showed that the GSTM1-null polymorphism was 73.8% in African-Americans (Weiserbs et al, 2003).…”
Section: Discussionsupporting
confidence: 62%
“…The DNA was stored at -20°C until amplified by the polymerase chain reaction (PCR) method in order to verify the eNOS polymorphism. To avoid contamination of the samples, the analysis was performed in an appropriate laminar flow according to the protocol proposed by Frare et al (2013).…”
Section: Methodsmentioning
confidence: 99%
“…The whole procedure was conducted in a laminar flow hood to minimize contamination. The final volume of the PCR was 25 µL according to the protocol proposed by Frare et al (2013).…”
Section: Methodsmentioning
confidence: 99%